Deproteinization of caries-affected dentin with chemo-mechanical caries removal agents and its effect on dentin bonding with self-etch adhesives. (June 2021) - Kusumasari, Citra; Abdou, Ahmed; Nakajima, Masatoshi; Tagami, Junji
Abstract: Objectives: To evaluate the micro-tensile bond strength (μTBS) of self-etch adhesives (SEA) to normal and caries-affected dentin after smear layer deproteinization with papain enzyme-based and NaOCl-based chemo-mechanical caries removal agents (CRAs) and to compare their efficacy to a 6 % NaOCl solution. Methods: Forty extracted human molars with occlusal carious lesions were randomly divided into four pretreatment groups: no treatment (control), Papacarie for 60 s, Carisolv for 60 s, and 6 % NaOCl for 15 s. After pretreatment, Universal Bond Quick ER (UBQ, one-step, 1-SEA) or Clearfil SE Bond 2 (CSE, two-step, 2-SEA) was applied to the pre-treated surface, and built-up with resin composite (Clearfil AP-X). The μTBS test was performed after 24 h water storage of the specimens at 37 °C, and the modes of failure were determined under SEM. Deproteinizing effects of the tested agents on smear layer-covered dentin was quantified by changes in the amide:phosphate ratio using attenuated total reflectance Fourier-transform infrared spectroscopy (ATR-FTIR) analysis. Results: On caries-affected dentin the μTBS improved significantly after pretreatment with Papacarie, Carisolv, and 6 % NaOCl with both SEAs ( p  < 0.05). Papacarie pretreatment significantly improved the μTBS of UBQ on normal dentin compared to NaOCl pretreatment ( p  < 0.05). ATR-FTIR revealed that all agents significantly decreased the amide:phosphate ratio on the smear layer-covered normal and caries-affected dentin ( p  < 0.05). Conclusions: Smear layer deproteinizing with papain enzyme-based and NaOCl-based gel CRAs was effective in improving the micro-tensile bond strength of self-etch adhesives to caries-affected dentin. Clinical significance: Smear layer deproteinization with Papacarie (a papain enzyme-based gel) or Carisolv (a NaOCl-based gel) can improve the μTBS to normal and caries-affected dentin bonded with 2-step self-etch adhesives.